In situ intracellular calcium oscillations in osteocytes in intact mouse long bones under dynamic mechanical loading. Issue 4 (17th December 2013) - Jing, Da; Baik, Andrew D.; Lu, X. Lucas; Zhou, Bin; Lai, Xiaohan; Wang, Liyun; Luo, Erping; Guo, X. Edward
Abstract : Osteocytes have been hypothesized to be the major mechanosensors in bone. How in situ osteocytes respond to mechanical stimuli is still unclear because of technical difficulties. In vitro studies have shown that osteocytes exhibited unique calcium (Ca 2+ ) oscillations to fluid shear. However, whether this mechanotransduction phenomenon holds for in situ osteocytes embedded within a mineralized bone matrix under dynamic loading remains unknown. Using a novel synchronized loading/imaging technique, we successfully visualized in real time and quantified Ca 2+ responses in osteocytes and bone surface cells in situ under controlled dynamic loading on intact mouse tibia. The resultant fluid‐induced shear stress on the osteocyte in the lacunocanalicular system (LCS) was also quantified. Osteocytes, but not surface cells, displayed repetitive Ca 2+ spikes in response to dynamic loading, with spike frequency and magnitude dependent on load magnitude, tissue strain, and shear stress in the LCS. The Ca 2+ oscillations were significantly reduced by endoplasmic reticulum (ER) depletion and P2 purinergic receptor (P2 R)/phospholipase C (PLC) inhibition. This study provides direct evidence that osteocytes respond to in situ mechanical loading by Ca 2+ oscillations, which are dependent on the P2 R/PLC/inositol trisphosphate/ER pathway. This study develops a novel approach in skeletal mechanobiology and also advances our fundamental knowledge of bone mechanotransduction.—Jing, D., Baik, A. D., Lu, X. L., Zhou, B., Lai, X., Wang, L., Luo, E., Guo, X. E. In situ intracellular calcium oscillations in osteocytes in intact mouse long bones under dynamic mechanical loading. FASEB J. 28, 28–1582 (1592). www.fasebj.org